How a Results-Based Financing approach can contribute to the health Sustainable Development Goals - Policy-oriented lessons: what we know, what we need to know and don't yet know - Jacky Mathonnat; Aurore Pelissier (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
The 'results-based financing' (RBF) approach, an umbrella term, occupies a particularly important place in the debates regarding meeting the challenge of 'better health for all at all ages' as stated in the Sustainable Development Goals 3. Our analysis of the RBF schemes results published in the literature underlines five major points. 1. The RBF approach is a very promising one, but highly context dependent. 2. There is no silver bullet. It should be based on a sound realistic theory of change with incentives relevant to the specificity of every context. 3. RBF includes not only financial incentives and can contribute to the reform of the health care system. 4. It appears very important to combine RBF on both the supply side and demand side (as conditional cash transfers, vouchers, etc.) to create positive synergies. 5. There are many gray areas on issues important to decision-makers. More rigorous research (including qualitative) is needed to create valuable public goods on this crucial issue.
Keywords: 330; objectifs de développement durable; santé; Health; Sustainable development goals